2015
DOI: 10.3892/etm.2015.2538
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-20a enhances the epithelial-to-mesenchymal transition of colorectal cancer cells by modulating matrix metalloproteinases

Abstract: Abstract. The mortality rates associated with colorectal cancer (CRC) are high due to metastasis. Epithelial-to-mesenchymal transition (EMT) is a key step in tumor metastasis. The aim of the present study was to investigate the function of microRNA-20a (miR-20a) in EMT. The expression of miR-20a was analyzed in CRC tissues and cell lines using the reverse transcription-quantitative polymerase chain reaction. Plasmids containing miR-20a short hairpin RNA and miR-20a mimics were transfected into SW620 and LS174T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 28 publications
3
43
0
1
Order By: Relevance
“…Among this cluster, miR-20a is a known oncogenic miRNA, thought be critically associated with enhanced EMT properties in colon cancer [40] and cisplatin-resistant phenotype in gastric cancer [41]. In CC cells, overexpression of miR-20a facilitates the proliferation and metastasis of CC [39].…”
Section: Discussionmentioning
confidence: 99%
“…Among this cluster, miR-20a is a known oncogenic miRNA, thought be critically associated with enhanced EMT properties in colon cancer [40] and cisplatin-resistant phenotype in gastric cancer [41]. In CC cells, overexpression of miR-20a facilitates the proliferation and metastasis of CC [39].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor metastasis is a complex process, and is highly regulated by multiple mechanisms, including aberrant activation of the phosphoinositide 3-kinase (PI3K)/AKT and transforming growth factor (TGF)-β/Smad pathways (8)(9)(10)(11). Furthermore, a large number of studies have shown that matrix metalloproteinase (MMP) overexpression is involved in numerous malignant tumors, including esophageal cancer, breast cancer, liver cancer and rectal cancer (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…miR-20a has been reported to be a tumor promoter in many cancers. Overexpression of miR-20a in these cancers enhances tumor growth and metastasis [33,34]. More importantly, previous research indicates that miR-20a induces cisplatin resistance in some cancer [35,36].…”
Section: Discussionmentioning
confidence: 99%